Modele polityki społecznej państwa a społeczna odpowiedzialność przedsiębiorstw - Rojek-Nowosielska, Magdalena (Models of Social Policy of a Country and Corporate Social Responsibility, 2009)
The aim of the article is to present some factors of development of corporate social responsibility. The main emphasis is on the models of social policy which create the scopes of the concepts of Corporate Social Responsibility coming into existence and functioning in a country.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 89-97